Home Values and Firm Behavior - Bahaj, Saleem; Foulis, Angus; Pinter, Gabor (American Economic Review, 2020)
The homes of firm owners are an important source of finance for ongoing businesses. We use UK microdata to show that a £1 increase in the value of the homes of a firm’s directors increases the firm’s investment by £0.03. This effect is concentrated among firms whose directors’ homes are valuable relative to the firm’s assets, that are financially constrained, and that have directors who are personally highly levered. An aggregation exercise shows that directors’ homes are as important as corporate property for collateral driven fluctuations in aggregate investment demand. (JEL D22, D25, E22, G31, G34, R31)